2010
DOI: 10.1007/s11095-010-0077-y
|View full text |Cite
|
Sign up to set email alerts
|

Release of Plasmid DNA-Encoding IL-10 from PLGA Microparticles Facilitates Long-Term Reversal of Neuropathic Pain Following a Single Intrathecal Administration

Abstract: Purpose Interleukin-10 (IL-10) is an anti-inflammatory molecule that has achieved interest as a therapeutic for neuropathic pain. In this work, the potential of plasmid DNA-encoding IL-10 (pDNA-IL-10) slowly released from biodegradable microparticles to provide long-term pain relief in an animal model of neuropathic pain was investigated. Methods PLGA microparticles encapsulating pDNA-IL-10 were developed and assessed both in vitro and in vivo. Results In vitro, pDNA containing microparticles activated mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 75 publications
4
59
0
Order By: Relevance
“…Further support for such an inflammation-mediated regulation of BSCB/BBB function is that, while proinflammatory molecules promoted the openings of BSCB, antiinflammatory cytokines, TGF-␤1 or IL-10, which have been shown to be able to inhibit spinal microglial activation and to reduce the expression of proinflammatory molecules (Moore et al, 2001;Echeverry et al, 2009;Soderquist et al, 2010), prevented the disruption of BSCB triggered by nerve injury. These antiinflammatory cytokines were effective in relieving experimental neuropathic pain (Echeverry et al, 2009;Soderquist et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Further support for such an inflammation-mediated regulation of BSCB/BBB function is that, while proinflammatory molecules promoted the openings of BSCB, antiinflammatory cytokines, TGF-␤1 or IL-10, which have been shown to be able to inhibit spinal microglial activation and to reduce the expression of proinflammatory molecules (Moore et al, 2001;Echeverry et al, 2009;Soderquist et al, 2010), prevented the disruption of BSCB triggered by nerve injury. These antiinflammatory cytokines were effective in relieving experimental neuropathic pain (Echeverry et al, 2009;Soderquist et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Systemic IL-1␤-induced alterations in BSCB can be mediated through a direct interaction with the IL-1␤ receptor located in the endothelium (Konsman et al, 2004) or indirectly, through IL-1␤-stimulated release of other chemokines having their corresponding recep- tors on blood vessels (Shaw and Greig, 1999;Ubogu et al, 2006). Further support for such an inflammation-mediated regulation of BSCB/BBB function is that, while proinflammatory molecules promoted the openings of BSCB, antiinflammatory cytokines, TGF-␤1 or IL-10, which have been shown to be able to inhibit spinal microglial activation and to reduce the expression of proinflammatory molecules (Moore et al, 2001;Echeverry et al, 2009;Soderquist et al, 2010), prevented the disruption of BSCB triggered by nerve injury. These antiinflammatory cytokines were effective in relieving experimental neuropathic pain (Echeverry et al, 2009;Soderquist et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Here we found that gene expression of both the algesic IL-6 [40,43] and the analgesic IL-10 cytokine [52,55] was increased in sural nerve specimens of patients with painful compared to painless neuropathies. IL-6 and IL-10 are both produced in Schwann cells, macrophages and T-lymphocytes in peripheral nerve.…”
Section: Discussionmentioning
confidence: 74%
“…iii) The use of intrathecal viral vectors or plasmid delivery to increase appropriate antihyperalgesic targets has been shown to have utility. Thus, increased spinal expression of IL-10 (anti-inflammatory cytokine)or plasmid delivery was anti-hyperalgesic [424,[429][430][431]. Increasing MAPK (Mitogen activated protein kinase) phosphatase-1 reduces activation of P38 MAPKs and this resulted in reduced nerve injury-evoked increases in inflammatory cytokines and chemokines and hyperalgesia [432].…”
Section: Gene-based Approachesmentioning
confidence: 99%